TEACHING NARRATIVE READING TEXT BY USING SQ3R AND ETR STRATEGIES TO THE EIGHTH GRADE STUDENTS OF MTS PARADIGMA PALEMBANG - Raudhatul Jannah (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2016)
In doing this study, the writer used pretest-posttest two treatment design. The population of this study was the eighth grade students of MTs Paradigma Palembang in academic year 2014/2015. The writer was assisted the class VIII.a as the first experimental group, class VIII.b as the second experimental group and class VIII.c as control group. There were 90 students taken as sample. Each class consisted of 30 students. The writer used independent sample t-test and one way annova to analyze the data. The result showed that teaching narrative reading by using SQ3R strategy was ,ore affective than ETR strategy. It can be seen from the mean score of the first experimental group (72.6667) was higher score than the second experimental group (64.2500). From the table analysis, the findings showed that: (1) there was a significant difference on narrative reading text achievement between the students who are taught by using SQ3R strategy and those are not. It was found that the p-output was 0.000 and t-obtained was 6.879; (2) there was a significant difference on narrative reading text achievement between the students who are taught by using ETR strategy and those are not. It was found that the p-output was 0.008 and t-obtained was 2.737. From the first and second hypotheses, The result was consulted to t-table at significance level 0.05 and critical value of t-table (1.672) in two tailed testings. Since the p-output was lower than 0.05 and t-obtained was higher than critical value of t-table, so, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted; and (3) there was a significant difference on students’ narrative reading text achievement between those who are taught by using SQ3R strategy, ETR strategy, and the teacher’s method. It was found that the p-output was 0.000 and F-obtained was 20.366. The result was consulted to t-table at significance level 0.05 and critical value of t-table (1.663) in two tailed testings. Since the p-output was lower than 0.05 and F-obtained was higher than critical value of t-table, so, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted